Laughter and smiling: sequential resources for managing delayed and disaligning responses. Issue 4 (2nd October 2021) - Looney, Stephen Daniel; He, Yingliang
ABSTRACT: This paper investigates the use of laughter and smiling to manage (dis)affiliation during two types of disturbances in the interactional unfolding of classrooms: delayed and disaligning responses. The analysis reveals that the sequential position and embodied turn design are integral to understanding the (dis)affiliative work laughter and smiling do. Around delayed responses, a teacher and students smile and produce standalone laughter that orients to students not responding promptly in teacher-initiated sequences as well as to subsequent actions of the teacher. Following disaligning responses, students produce standalone laughter that orients affiliatively to the non-serious nature of disaligning turns. In contrast, the teacher's interpolated particles of aspiration and smile voice, while recognising the playfulness of disaligning turns, is more disaffiliative and precedes turns in which the teacher redirects the nature of the interaction seriously. Thus, the work that laughter does is not necessarily purely affiliative or disaffiliative but falls on a spectrum of (dis)affiliation. The analysis suggests that laughter and smiling are key resources in the management of sensitive moments in classroom interaction involving uncertainty, the mitigation of sensitive actions, and (dis)affiliation.